An Analysis of the Friezes at Huaca del Dragón - (:unkn) unknown (My University, 2024)
The archaeological site of Huaca del Dragón, located near modern Trujillo, Peru, was constructed by the Chimú civilization in the tenth or eleventh century CE. The site is named for the low-relief imagery that decorates its walls, the central motifs of which are interpreted as dragons and rainbows. These images diverge from much of the visual and material culture produced by the Chimú. Interpretations of the imagery at Huaca del Dragón have been debated by scholars for decades. While the relief decoration seems enigmatic, this analysis considers both iconography and style to argue that the friezes reflect on a visual tradition practiced throughout the North Coast of Peru and its surrounding regions for hundreds of years. This project illustrates the evolution of the motifs and asserts that they function as evidence of cultural continuity in the Andes. While a definite meaning of the relief decoration at Huaca del Dragón cannot be determined by modern scholars, this project connects specific concepts of pre-Hispanic Andean worldview to the frieze imagery in order to illuminate its possible conceptual motivations. This results in an exploration of what the relief imagery may have meant to its artists, patrons, and intended audiences, and an interpretation of the iconography as related to the conception of natural phenomena as mythical beings.
Keywords: Andes; Dragon; Huaca del Dragón; Peru; Rainbow